Coral Reef in SAP of Western Waigeo Island in Raja Ampat District - dudi lesmana (Universitas Djuanda, 2018)
This study aims to identify the condition of coral reefs in SAP Western Waigeo Islands, Raja Ampat District. The value of coral cover in the SAP area of the Western Waigeo Islands is in the range of 0% to 60% with an average value of 25.02%. In general, the condition of coral reefs in SAP Western Waigeo Islands can be categorized as